What Are Animals Worth? Review of Animals and Capital by Dinesh Joseph Wadiwel (2023) - Guha-Majumdar, Jishnu (Humanimalia, 2024)
Review of:Dinesh Joseph Wadiwel, Animals and Capital. Animalities. Edinburgh: Edinburgh University Press, 2023. xii + 316 pp. 3 b/w illus. £95.00 (hb).